Users, Gender, and Access: Ottawa's Public Transportation History from 1891 to 2011 - Gann, Emily (Université d'Ottawa | University of Ottawa, 2024)
Users, Gender, and Access: Ottawa's Public Transportation History from 1891 to 2011 is a study focused on mobility technologies and services, changing passenger demographics, and issues of access. This work spans from 1891, when electric streetcars were first introduced in the City of Ottawa, to 2011, when OC Transpo's fleet was deemed fully accessible as its conventional fleet was entirely made up of low-floor buses. Over this period, the city and its public transportation offerings witnessed and responded to notable changes in passenger demographics, disability-led legislation regarding design and access, and fluctuations, growth, and resistance to established and new relationships between gender, users, and mobility technologies. This study is informed by critical concepts and frameworks from Feminist Technology Studies, Feminist Disability Studies, and Science and Technology Studies. As a collective, these studies inform a fluid appreciation of the nuanced and intricate ways in which technology and users shape and are shaped by one another, with respect to different spaces, places, and time periods. These insights support Users, Gender, and Access's attempt to understand and appreciate more recent gendered experiences of urban mobility within the history, legacy, and context of the need, development, and purpose of Ottawa's early public transportation efforts. In order to explore this history, this study relies on a rich variety of primary sources through a mix-method approach. Archival material pulled from the City of Ottawa Archives, as the primary repository for the city's operational material, alongside oral history interviews and first-person perspectives presented in newspapers offer unique insights for this work. These sources are studied alongside the rich material culture provided by a number of key artifacts and technologies, which ground this study in the built environment and sensorial experience of mobility. Ultimately, Users, Gender, and Access presents a case study for examining the history of access and inclusion, or a lack there of, which is informed by the fluid relationship between users and technology. It offers a unique contribution to the wider fields of transportation, material culture, gender, and disability by demonstrating the value of tracing the history of socio-technical artifacts. As this work argues, decision made in the late 1800s, that were informed by gendered and ableist appreciations of urban mobility and the role of public transportation, continue to influence how this technology is appreciated and experienced in the present.
Keywords: Gender; Access; Mobility; Material culture; Feminist technology studies